Differential performance in CP dissemination in Colombia and Mexico (2018)
Cleaner production (CP) is a strategy to improve environmental and economic performance of firms through the implementation of preventive practices and cleaner technologies. For decades, scholars and practitioners of private and public institutions have recognized its promise to enhance firm sustainability and productivity; however, challenges for CP dissemination remain, particularly among small and medium-sized enterprises (SME). This research aims to study the outcomes in the application of a CP dissemination model in two different countries, in order to understand whether differences arise and, if so, why they occur. Comparing the experience of Mexico and Colombia, through econometric models, offers the opportunity to gauge how internal and external factors influence the coverage, performance and capacity building outcomes of a similar CP dissemination model. By comparing a similar model in different contexts, the article suggests that supply chain approaches can be an effective way of disseminating cleaner production. The article notes possible implications that may contribute to greater implementation of innovation for sustainable development and green growth.